7d-3d+5d-5-6d=0

Simple and best practice solution for 7d-3d+5d-5-6d=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7d-3d+5d-5-6d=0 equation:


Simplifying
7d + -3d + 5d + -5 + -6d = 0

Reorder the terms:
-5 + 7d + -3d + 5d + -6d = 0

Combine like terms: 7d + -3d = 4d
-5 + 4d + 5d + -6d = 0

Combine like terms: 4d + 5d = 9d
-5 + 9d + -6d = 0

Combine like terms: 9d + -6d = 3d
-5 + 3d = 0

Solving
-5 + 3d = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 3d = 0 + 5

Combine like terms: -5 + 5 = 0
0 + 3d = 0 + 5
3d = 0 + 5

Combine like terms: 0 + 5 = 5
3d = 5

Divide each side by '3'.
d = 1.666666667

Simplifying
d = 1.666666667

See similar equations:

| b-2+3b+64=4 | | -136=8(1+6b) | | 16=2(x-1)-4 | | 4(3x+5)=104 | | 7.50=0.8c+0.5c | | 11=-7p+13+8p | | 6x-50=10-x | | 2m+23=7m-2 | | 0.5c-7.50= | | x^2-3x+24=0 | | 17x^2-22x+6=0 | | -4x+-40-6=-3-6 | | 4+4b=4 | | 7n-18+1=19 | | 8.2(s+4)=6.7x+5.2 | | b-2+3b+6=4 | | 6p-1=p+20 | | 6(x+8)=7X+3 | | 27*x=1800 | | 6(X+8)=7x-3 | | -6+3X-3Y=0 | | 0=-Y+X-4 | | -3+2X=Y | | 7x+5x+10= | | y+5=-10(X-1) | | 18x^2-47x-56=0 | | 3+(5a+5)=35 | | -1-9x=9x+19 | | 15*x^10=67 | | 7(4b-1)=-3b-2 | | 3(2m-10)=2m+10 | | 20=14m-9+3(5m) |

Equations solver categories